Association of trauma, post-traumatic stress disorder and non-affective psychosis across the life course: a nationwide prospective cohort study. Issue 4 (20th March 2023) - Allardyce, Judith; Hollander, Anna-Clara; Rahman, Syed; Dalman, Christina; Zammit, Stan
Abstract: Background: We aimed to examine the temporal relationships between traumatic events (TE), post-traumatic stress disorder (PTSD) and non-affective psychotic disorders (NAPD). Methods: A prospective cohort study of 1 965 214 individuals born in Sweden between 1971 and 1990 examining the independent effects of interpersonal and non-interpersonal TE on incidence of PTSD and NAPD using data from linked register data (Psychiatry-Sweden). Mediation analyses tested the hypothesis that PTSD lies on a causal pathway between interpersonal trauma and NAPD. Results: Increasing doses of interpersonal and non-interpersonal TE were independently associated with increased risk of NAPD [linear-trend incidence rate ratios (IRR)adjusted = 2.17 [95% confidence interval (CI) 2.02–2.33] and IRRadjusted = 1.27 (95% CI 1.23–1.31), respectively]. These attenuated to a relatively small degree in 5-year time-lagged models. A similar pattern of results was observed for PTSD [linear-trend IRRadjusted = 3.43 (95% CI 3.21–3.66) and IRRadjusted = 1.45 (95% CI 1.39–1.50)]. PTSD was associated with increased risk of NAPD [IRRadjusted = 8.06 (95% CI 7.23–8.99)], which was substantially attenuated in 5-year time-lagged analyses [IRRadjusted = 4.62 (95% CI 3.65–5.87)]. There was little evidence that PTSD diagnosis mediated the relationship between interpersonal TE and NAPD [IRRadjusted = 0.92 (percentile CI 0.80–1.07)]. Conclusion: Despite the limitations to causal inference inherent in observational designs, the large effect-sizes observed between trauma, PTSD and NAPD in this study, consistent across sensitivity analyses, suggest that trauma may be a component cause of psychotic disorders. However, PTSD diagnosis might not be a good proxy for the likely complex psychological mechanisms mediating this association.